Chemical Vapor Deposition - Recent Advances and Applications in Optical, Solar Cells and Solid State Devices 2016
DOI: 10.5772/63926
|View full text |Cite
|
Sign up to set email alerts
|

Non-Classical Crystallization of Thin Films and Nanostructures in CVD Process

Abstract: Non-classical crystallization, where crystals grow by the building blocks of nanoparticles, has become a significant issue not only in solution but also in the gas phase synthesis such as chemical vapor deposition (CVD). Recently, non-classical crystallization was observed in solution in-situ by transmission electron microscope (TEM) using a liquid cell technique. In various CVD processes, the generation of charged nanoparticles (CNPs) in the gas phase has been persistently reported. Many evidences supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…as shown in Figure b, which was observed in a series of CVD experiments and is possibly due to irregularity of the substrate surface (mechanical defects). In view of the well-defined morphology of the rest of the samples, this is not likely a purely thermal effect, rather provides a hint toward electrostatic interactions that may, for example, arise from the difference in conductivity or surface defects as a result of varying surface roughness in either of the two growth regimes …”
Section: Resultsmentioning
confidence: 53%
“…as shown in Figure b, which was observed in a series of CVD experiments and is possibly due to irregularity of the substrate surface (mechanical defects). In view of the well-defined morphology of the rest of the samples, this is not likely a purely thermal effect, rather provides a hint toward electrostatic interactions that may, for example, arise from the difference in conductivity or surface defects as a result of varying surface roughness in either of the two growth regimes …”
Section: Resultsmentioning
confidence: 53%
“…This leads to fractal growth. In the extreme case, for high concentrations of NaCl (concentration greater than 4 and 5 mg•ml −1 ), the X/M ratio decreases even further and results in a condition close to diffusion limited aggregation [28,41]. The rate of attachment in this case is much higher than the rate of diffusion and as shown in figures 2, 3 and 10, the substrate has a high areal coverage of multi-layers as well as a high density of dendrites visible in multi-layer contrast images.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical predictions tend to deviate significantly from experimental results in orders of magnitude in nucleation and reaction rates of the crystalline particles. Different experimental studies and approaches demonstrated empirically multiple possible formation pathways toward the final crystal through the inclusion of prenucleation clusters, liquid droplets, gels, primary amorphous or crystalline nanoparticles, nanoaggregates, or mesocrystals . In the past two decades, a large variety of these transitional precursor phases of crystalline substances were discovered in pharmaceuticals, , proteins, organic molecules, , thin films, , biominerals, , and inorganic materials. ,, …”
Section: Introductionmentioning
confidence: 99%